Loss of platelet BMP4 reduces vascular inflammation and ameliorates vascular remodelling after carotid wire injury. (25th November 2020) - Zhou, Q; Jank, M; Von Niessen, N; Olivier, C.B; Schmitt, H; Anto-Michel, N; Hilgendorf, I; Bode, C; Moser, M
Abstract: Background: Bone morphogenic proteins (BMPs) are members of the TGFβ superfamily. They have distinct functions during hemostasis and play a central role in various pathologic conditions, including cardiovascular diseases. Recent findings demonstrate that BMPs are also expressed in platelets. However, their function is poorly understood. Here, we investigate the role of platelet BMP4 during vascular inflammation and vascular remodelling. Methods: BMP4 floxed mice were crossed with PF4 Cre mice to generate platelet-specific deletion of BMP4 (BMP4Plt−/−). Intravital microscopy of mesenteric veins was performed to evaluate leukocyte adhesion upon stimulation with TNFα. Expression of adhesion molecules and chemokines were analysed by RT-PCR and Western Blot. P-selectin and platelet-leukocyte aggregates were evaluated using flow cytometry. For carotid wire injury, BMP4Plt−/− were further crossed with LDLr−/− mice (BMP4Plt−/−/LDLr−/−). At 8 weeks of age, BMP4Plt−/−/LDLr−/− mice and control littermates received a 2-week diet containing 15.8% wt/wt fat and 1.25% cholesterol. Carotid wire injury was performed at the age of 10 weeks. Re-endothelialisation and neointimal hyperplasia were evaluated. Results: Platelet morphology and function did not differ between BMP4Plt−/− and control mice. Stimulation with TNFα resulted in increased rolling and adherence of leukocytes to the vessel wall which was reduced in BMP4Plt−/− mice (175±25 versus 50±7 rolling cells and 16±3 versus 7±2 adherent cells, respectively). Expression of P-selectin, adhesion molecules and the chemokines RANTES and PF-4 were reduced in BMP4Plt−/− mice. Platelet activation by thrombin was reduced in BMP4Plt−/− mice, resulting in diminished P-Selectin and JONA expression. Furthermore, monocyte infiltration and circulating leukocyte-platelet complexes were reduced in BMP4Plt−/− mice. Loss of platelet BMP4 prevented neointima formation after carotid wire injury (4.2x104±0.9x104μm 2 versus 14.9x104±2.2x104μm 2 in BMP4Plt−/−/LDLr−/− and control mice, respectively). Interestingly, endothelial regeneration after injury was decelerated in BMP4Plt−/− mice. This is further demonstrated in-vitro, where platelet BMP4 promoted endothelial cell proliferation and migration. Conclusion: Platelet-BMP4 deficiency reduced vascular inflammation and ameliorated intima hyperplasia after wire injury. This is partly mediated by inhibition of platelet activation, reduced expression of adhesion molecules and inflammatory response. Our finding suggests that BMP4 is a promising target for the treatment of vascular inflammation and restenosis. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): Else-Kröner Fresenius Foundation; German Cardiac Society